2020
DOI: 10.3390/nano10112287
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Aided Design of Microtextured Surfaces: Application to Controlling Wettability

Abstract: Artificial intelligence (AI) has emerged as a powerful set of tools for engineering innovative materials. However, the AI-aided design of materials textures has not yet been researched in depth. In order to explore the potentials of AI for discovering innovative biointerfaces and engineering materials surfaces, especially for biomedical applications, this study focuses on the control of wettability through design-controlled hierarchical surfaces, whose design is supported and its performance predicted thanks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Another critical aspect of micropatterning is the utilization of data-driven techniques for pattern design [257]. Artificial intelligence has proven instrumental in engineering innovative hierarchical structures and multiscale surfaces with controlled functionality [258,259]. In conjunction with the existing literature, substantial advancements have been made by integrating machine learning and data-driven methodologies to comprehend and achieve diverse micropatterns.…”
Section: Discussionmentioning
confidence: 99%
“…Another critical aspect of micropatterning is the utilization of data-driven techniques for pattern design [257]. Artificial intelligence has proven instrumental in engineering innovative hierarchical structures and multiscale surfaces with controlled functionality [258,259]. In conjunction with the existing literature, substantial advancements have been made by integrating machine learning and data-driven methodologies to comprehend and achieve diverse micropatterns.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) aided design can be used to fabricate textured surfaces with hierarchical topography and can be able to predict the wettability of the materials. 236 Studies have also indicated that digital tomography-trained AI-based models can predict scaffolds’ mechanical properties with different geometries. 237 Goh et al , in a recent review, highlighted four categories (supervised, unsupervised, semi-supervised, and reinforced) of machine learning and their applicability in 3D printing.…”
Section: Future Scopesmentioning
confidence: 99%
“…Controlling wettability through design-controlled hierarchical surfaces or microtextured biointerfaces, whose design is aided by Artificial Neural Networks and whose performance is predicted (ANN). To build design maps for super hydrophobic polymer topographies, [26] used a hybrid approach that included experimental methodologies, numerical simulations, and machine learning (ML) algorithms. The maximum water contact angle (WCA) and Laplace pressure were two super hydrophobic properties studied.…”
Section: Machine Learning Models For Tuning the Nanomaterialsmentioning
confidence: 99%